RANCANG BANGUN MESIN DISTRIBUSI COR INSULASI PERLIT PADA MODULAR PERTASHOP - Bagus Brillian Putra Kharisma; Tri Andi Setiawan; Fais Hamzah (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
State-owned oil and gas companies coorporate with manufacturing companies that have been recommended to make Pertashop modular. PT. INKA Multi Solusi is one of the fabricators that produces Pertashop modular. In 2022 PT. INKA Multi Solusi plans to produce 1000 units the demand for Pertashop needsthroughout Indonesia. Pertashop fabrication process at PT. INKA Multi Solusi there are stages of the perlite insulation process on the side between the inner tank and outer tank which is carried out by 6 workers manually, by lifting the results of the cast mixer with a reservoir and then pouring it into the modular. The average time required for perlite insulation is 1 hour 15 minutes, so it is necessary to have an auxiliary machine for the distribution process of perlite insulation concrete to increase production effectiveness. The process of making machines using the Ulrich method starts from identifying consumer needs, determining design concepts, selecting design concepts, carrying out the fabrication process and testing machines. In testing this machine is able to distribute perlit concrete material as far as 2 meters vertically and 2 meters horizontally with an output capacity of 4 kg/minute with a total budget of Rp. 11.849.000,-